2015
DOI: 10.1080/2162402x.2015.1008814
|View full text |Cite
|
Sign up to set email alerts
|

Trial Watch: Immunomodulatory monoclonal antibodies for oncological indications

Abstract: These authors contributed equally to this work. Keywords: ipilimumab, MEDI4736, MPDL3280A, nivolumab, pembrolizumab, urelumab Abbreviations: CRC, colorectal carcinoma; CTLA4, cytotoxic T lymphocyte-associated protein 4; FDA, Food and Drug Administration; IL, interleukin; KIR, killer cell immunoglobulin-like receptor; mAb, monoclonal antibody; NK, natural killer; NSCLC, nonsmall cell lung carcinoma; PD-1, programmed cell death 1; RCC, renal cell carcinoma; TGFb1, transforming growth factor b1; TLR, Toll-like re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 214 publications
0
71
0
Order By: Relevance
“…In accordance with other studies, we showed that chemotherapy-induced shortterm benefits 27,28 and, in addition with data from clinical trial using immune-based therapies, [29][30][31][32] our results strongly demonstrate that a strong adaptive immune reaction within the tumor is associated with long-term survival for the patients. This could bring some additional evidence to the significant long-term clinical benefits of the immune checkpoint blockade 30,33 or the rituximab treatment, 34 but with contrasted short-term effects. In NSCLC, immunotherapy is a very promising therapeutic approach as reflected by the satisfactory and long-lasting response rates obtained in recent trials targeting the PD1/PD-L1 immunosuppressive pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with other studies, we showed that chemotherapy-induced shortterm benefits 27,28 and, in addition with data from clinical trial using immune-based therapies, [29][30][31][32] our results strongly demonstrate that a strong adaptive immune reaction within the tumor is associated with long-term survival for the patients. This could bring some additional evidence to the significant long-term clinical benefits of the immune checkpoint blockade 30,33 or the rituximab treatment, 34 but with contrasted short-term effects. In NSCLC, immunotherapy is a very promising therapeutic approach as reflected by the satisfactory and long-lasting response rates obtained in recent trials targeting the PD1/PD-L1 immunosuppressive pathway.…”
Section: Discussionmentioning
confidence: 99%
“…1012 Despite such advances, several challenges exist with use of immune checkpoint agents, including variable response rates in less than half of patients with advanced melanoma (and with even lower efficacy against other cancers deemed ‘less immunogenic’), potential effects on newly discovered immune checkpoint pathways intrinsic to tumor cells, and potential effects on T eff cell homing. 11,13 Importantly, emerging data now implicates defects in T eff cell homing as a critical factor in resistance to immune checkpoint blockade.…”
Section: Introductionmentioning
confidence: 99%
“…25 Notably, the expression of CD274 (a potent immunosuppressive molecule also known as PD-L1) by MDSCs and other immunosuppressive myeloid cells also depends on STAT3. 26 This latter observation suggests that STAT3 inhibition may downregulate PD-L1, implying that combining AZD9150 with checkpoint blockers 27,28 targeting the interaction between PD-L1 and its main receptor (programmed cell death 1, PDCD1, best known as PD-1) may not be useful. However, this conjecture remains to be investigated at the experimental level.…”
mentioning
confidence: 98%